EFEKTIVITAS MODEL INTERAKSI SOSIAL TERHADAP SIKAP TOLERANSI DAN KETERLIBATAN SISWA DALAM PEMBELAJARAN TEMATIK DI SD - Melati (Jurnal Komunikasi, 2026)
This study aims to analyze the effectiveness of implementing the social interaction model on students' tolerance attitudes and engagement in thematic learning in elementary schools. Thematic learning requires the integration of students’ cognitive, affective, and social aspects; therefore, a learning model that facilitates positive interaction among students is needed. This research employed a quantitative approach with a quasi-experimental design. The research subjects were fourth-grade elementary school students. Data collection techniques included a tolerance attitude questionnaire, student engagement observation sheets, and learning outcome tests. The results of the study indicate that the implementation of the social interaction model is effective in improving students' tolerance attitudes and engagement in the thematic learning process. This model encourages students to cooperate with one another, respect differences of opinion, and actively participate in learning activities.